Board Characteristics and Internal Control Risk Management in Urban Investment Companies: A Case Study of Guangxi Urban Investment Group - Wang, Su; ., ROZAINI; Wang, Zhen Gang (Journal of Ecohumanism, 2024)
This study explores the relationship between board characteristics and internal control effectiveness and risk management practices in Chinese urban investment companies. Using a mixed research method combining questionnaire surveys and case studies, an empirical study was conducted on 104 urban investment companies, with the Guangxi Urban Investment Group as a case study. The study found that board characteristics are significantly and positively correlated with internal control effectiveness and risk management practices. Among these, the impact of board expertise is the most significant, followed by board independence and diversity. Board size is positively correlated with internal control effectiveness, but has no significant relationship with risk management practices. The study also found that company size has a moderating effect on the relationship between board characteristics and governance practices. This study provides theoretical and practical guidance for the corporate governance of urban investment companies, emphasizing the importance of improving the professionalism, independence and diversity of the board of directors. The study suggests that urban investment companies should adjust the composition of the board of directors according to their size and complexity, and adopt a comprehensive governance framework to integrate internal control and risk management practices. Future research can further explore the relationship between board characteristics, governance practices and company performance, as well as the impact of emerging technologies on the governance requirements of urban investment companies.